2020
DOI: 10.7150/ijbs.38811
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Characterization and Discovery of Novel Genetic Mutations of Chinese Patients with COL2A1-related Dysplasia

Abstract: COL2A1-related disorders represent a heterogeneous group of skeletal dysplasias with a wide phenotypic spectrum. Our aim is to characterize the clinical and molecular phenotypes of Chinese patients with COL2A1-related dysplasia and to explore their phenotype-genotype relations. Clinical data were collected, physical examinations were conducted, and X-ray radiography and genetic analyses were performed in ten families involving 29 patients with COL2A1-related dysplasia. Nine mutations were identified in COL2A1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…S2 and Additional File 1 : Table S2). The variation had been reported to be the pathogenic variation of SEDC, regarded as a hot spot variation [ 4 9 ]. The genotype frequency in the 1000 Genomes Project, ESP and ExAC was less than 0.001.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S2 and Additional File 1 : Table S2). The variation had been reported to be the pathogenic variation of SEDC, regarded as a hot spot variation [ 4 9 ]. The genotype frequency in the 1000 Genomes Project, ESP and ExAC was less than 0.001.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, several manifestations, including disproportionate short stature and neck, spine malformation including scoliosis and kyphosis, acetabulum abnormal, and femoral head disease, were common symptoms among different families. The proband from Family 1 [ 9 ] had a pain, limitation in hip mobility and abnormal gait from 5 years old and the symptoms increased with age. Short heights, lower extremities and spines abnormal were his main clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with C-propeptide glycine substitutions have been reported to be shorter than those with N-propeptide substitutions ( Terhal et al, 2012 ). Our center has reported that glycine to serine substitution caused milder phenotypes than glycine to nonserine substitutions ( Xu et al, 2020 ). In Kniest dysplasia, the classical phenotypes are short-trunk dwarfism due to severely affected skeletal growth, scoliosis, platyspondyly, and joint enlargement, while extraskeletal features mainly include myopia, prominent eyes, conductive hearing loss, and mid-face hypoplasia ( Barat-Houari et al, 2016a ).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenicity is closely associated with mutations of the genes encoding collagen (e. g. type I, II, IX, IX, XI collagen) [3] . Current scienti c study reported many pathogenic gene variations in the proband with skeletal dysplasia and variants occurred in causative genes of COL1A1, COL1A2, WNT1, OBSL1, FGFR3, IMPAD1, FBN2, and GORAB [4][5][6] . According to 2019 edition of the Nosology, 461 disorders classi ed within 42 different groups have been described based on radiologic, molecular and biochemical criteria [7] .…”
Section: Introductionmentioning
confidence: 99%